Avaliação da funcionalidade em pacientes com doenças reumáticas atendidos pelo SUS em Minas Gerais no período de 2011-2019. - Elisa Neide Barbosa de Souza (2020)
Introduction: rheumatic diseases, Rheumatoid Arthritis (RA), Psoriatic Arthritis (AP) and Ankylosing Spondylitis (AE) are common, chronic inflammatory diseases with the potential for functional damage, with RA being the most frequent of the three diseases. The treatment of these health conditions aims to alleviate symptoms and minimize disease progression, improve functionality, quality of life and reduce morbidity and mortality. The treatment includes drug and non-drug therapy, and drug treatment includes the use of non-steroidal anti-inflammatory drugs (NSAIDs), corticosteroids, synthetic (MMCDs) and biological (MMCDb) disease-modifying drugs. Goals: to evaluate the functionality in a cohort of adult patients, using biological drugs incorporated by the Unified Health System (SUS), in Belo Horizonte / MG, for the treatment of RA, AP and EA in the period from 2011 to 2019. Methods: this is an open prospective cohort study conducted at the Regional Health Superintendence (SRS) of Belo Horizonte, Minas Gerais, of patients undergoing treatment for RA, AP and EA at SUS, undergoing treatment with MMCDb. The data was collected using a standardized form, prepared by the Pharmacoepidemiology Research Group (GPFE). Up to three interviews were conducted per patient, the first interview took place at the time of the first dispensing of the biological medication, and from then on, interviews were conducted every six months. Functionality was assessed using the Health Assessment Questionaire Disability Index (HAQ-DI) according to rheumatic disease, patient characteristics, disease duration and disease activity. Results: most participants were female (75,6%) and had RA (66.5%). The median HAQ-DI was 1.5 (0.8-1.9) at baseline and the highest values were observed in patients with RA. Multivariate analysis showed that the factors that were associated with a positive direct association with worse patient functionality were the highest disease activity (Clinical Disease Activity Index - CDAI), Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) and female sex at 6 months, and in 12 months, only BASDAI showed a positive association with HAQ-DI (p <0.001). A significant reduction in median HAQ-DI values was observed, with the best results observed in patients with AS. The remission status of HAQ-DI ≤0.5 was not observed in RA.The results showed a significant reduction in median HAQ-DI values, with the best results observed in patients with AS remission state (HAQ-DI values ≤ 0.5). The best effects were observed in six months of treatment for the three diseases. The variables female gender, age, time of disease, CDAI and BASDAI were independent and positively associated with the functionality measured by the HAQ-DI. The Minimal Clinical Diferene (MCID) was evaluated and changes in HAQ-DI values of 0,22 were considered as MCID. Conclusion: the use of MMCDb provided a significant improvement in functionality in most patients. More patients reached MCDI when comparing 12 months of treatment with the baseline. The factors that influenced the worsening of functionality were: female gender, longer disease duration and greater disease activity.